Students’ Readiness in Implementing Mobile Learning for English Language Learning Purposes - Muhammad Fathur Rahman Khalik; Nur Hidayanto Pancoro Setyo Putro (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2021)
Background: The application of mobile learning (m-learning), especially in the area of language learning, has gained interest in the last several years due to the benefits offered by mobile devices. However, to maximize the effectiveness of m-learning, students are required to be ready. Thus, it is crucial to assess students’ readiness before implementing m-learning. By focusing on rural schools, this quantitative study aims to examine students’ readiness in implementing m-learning in their English language learning. Methodology: This study employed a survey design to measure m-learning readiness of senior high school students by investigating three factors, namely mobile self-efficacy, optimism, and self-directed learning. Through an online questionnaire, 140 responses were successfully collected from students in two public senior high schools (one high school and one vocational high school) located in a rural area in Soppeng, Indonesia. The data collected were subsequently analyzed using SPSS Statistics ver. 25. Findings: The results revealed that senior high school students from a rural area in Soppeng, Indonesia, had a high level of self-efficacy and optimism in implementing m-learning in their English language learning. However, their self-directed learning was still at a moderate level. Moreover, further analysis showed that type of school significantly affected students’ mobile self-efficacy and optimism, while self-directed learning was not affected. Conclusion: Students from rural senior high schools in Soppeng, Indonesia, showed readiness in implementing m-learning for English language learning purposes.